Book review: Amit Kumar Gupta, Crises and Creativities: Middle Class Bhadralok in Bengal c. 1939–52, Parimal Ghosh, What Happened to the Bhadralok and Tanika Sarkar and Sekhar Bandyopadhyay, eds., Calcutta: The Stormy Decades. (April 2018) - Roy, Tirthankar
Amit Kumar Gupta, Crises and Creativities: Middle Class Bhadralok in Bengal c. 1939–52, Delhi: Orient BlackSwan, 2009, 320 pp. Parimal Ghosh, What Happened to the Bhadralok, Delhi: Primus Books, 2016, 200 pp. Tanika Sarkar and Sekhar Bandyopadhyay, eds., Calcutta: The Stormy Decades, Delhi: Social Science Press, 2015, 474 pp.